A social web platform based on semantics to share exam questions: the SOLE approach. (1st January 2011) - Colomo-Palacios, Ricardo; García-Crespo, Ángel; Jiménez-López, Diego; Blanco-Iglesias, Borja
Internet has changed dramatically leaning and teaching scenarios. As a consequence of this, learning resources are being produced, catalogued and stored using innovative ways, using social and Semantic Web, among others. SOLE provides a platform in which exam questions can be produced supported by Web 2.0 tools, catalogued and labelled via Semantic Web and stored and distributed using e-learning standards. This paper presents, SOLE, a social network of exam questions sharing particularised for software engineering domain, based on semantics and built using Semantic Web and e-learning standards, such as IMS question and test interoperability specification 2.1.